Laser dressing of resin-bond diamond grinding wheel. (25th June 2007) - Wang, Xuyue Y.; Kang, R.K.; Xu, W.J.; Wang, L.J.; Guo, D.M.
Laser processing of super-abrasive grinding wheel is paying a great role in a truing/dressing technique to complement mechanical methods. An energy balance model was developed that took into account the space mode of laser energy absorbed/scattered by the workpiece. Both geometric and mathematic models were developed to reveal laser processing mechanism and predict the processing parameters, such as incident power and focal offset, to perform material removal during laser processing a resin-bond diamond grinding wheel. Various trends of the geometrical features of dressing zone in terms of the varying focal offsets were analysed. The dressing method and its fundamental experiment are introduced, and processing performance through grinding-force measurement was tested. The analysis of calculating and experimental results has provided an in-depth understanding of the relation between processing parameters and dressing quality, forming a knowledge base that helps improve dressing techniques.